1994
DOI: 10.1128/mcb.14.9.5692
|View full text |Cite
|
Sign up to set email alerts
|

The delta-crystallin enhancer-binding protein delta EF1 is a repressor of E2-box-mediated gene activation.

Abstract: The repressor 8EF1 was discovered by its action on the DC5 fragment of the lens-specific 81-crystallin enhancer. C-proximal zinc fingers of 8EF1 were found responsible for binding to the DC5 fragment and had specificity to CACCT as revealed by selection of high-affinity binding sequences from a random oligonucleotide pool. CACCT is present not only in DC5 but also in the E2 box (CACCTG) elements which are the binding sites of various basic helix-loop-helix activators and also the target of an unidentified repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
197
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(203 citation statements)
references
References 44 publications
6
197
0
Order By: Relevance
“…1), binds CACCT-containing DNA, while the DC-fin form of dEF1 does not (Sekido et al 1994). From this result, we thought that C-fin was the major binding domain of the dEF1 molecule.…”
Section: Specificity Of Individual Dna Binding Domainsmentioning
confidence: 90%
“…1), binds CACCT-containing DNA, while the DC-fin form of dEF1 does not (Sekido et al 1994). From this result, we thought that C-fin was the major binding domain of the dEF1 molecule.…”
Section: Specificity Of Individual Dna Binding Domainsmentioning
confidence: 90%
“…In vertebrates, Zfhx1 proteins are classified as either ␦EF1 or Sip1. Functional analyses of ␦EF1 and Sip1 proteins from mouse and chicken have demonstrated their similarities: binding to an identical consensus sequence CACCT and acting as transcriptional repressors when bound (Sekido et al, 1994Remacle et al, 1999), by a mechanism involving the binding of co-repressor CtBP (Furusawa et al, 1999;van Grunsven et al, 2003). These proteins also participate in gene activation in other contexts (Lazarova et al, 2001;Dillner and Sanders, 2004;Yoshimoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the E1a ± CtBP interaction was required for the induction of epithelial gene expression. In the case of the E-cadherin promoter, this resulted from E1a's disruption of a complex involving CtBP and dEF1/ZEB, a zinc ®nger-homeodomain repressor protein (Sekido et al, 1994) that controls muscle and lymphoid di erentiation (Sekido et al, 1994;Higashi et al, 1997;. Anoikis-sensitivity resulted from the E1a ± CtBP interaction as well.…”
mentioning
confidence: 99%
“…The zinc ®nger-homeodomain repressor dEF1/ZEB binds E-boxes Rb-family Corbeil and Branton, 1994 D1 ± 140 p300, CBP, P/CAF, Rb Wang et al, 1993;Reid et al, 1998;Corbeil andBranton, 1994 D81 ± 243* Rb-family, CtBP Wang et al, 1993;Reid et al, 1998;Corbeil and Branton, 1994D202 ± 243 CtBP Boyd et al, 1993233PL?AS CtBP Boyd et al, 1993; this study *A C-terminal nuclear localization signal and HA-tag were appended to this coding sequence E1a mutants used in this study were previously characterized as indicated in the references, except the 233PL?AS mutant, which was shown to prevent the interaction of E1a with CtBP as follows. Gst-CtBP protein (2 mg; lanes 2 ± 4) or gst protein (lane 1) immobilized on glutathionesepharose was reacted in bu er containing 200 mM NaCl and 0.25% Triton X-100 with in vitro translated E1a wild-type (lanes 1 and 2), E1a P233A (lane 3) or E1a 233PL?AS (lane 4), washed and analysed by PAGE (Sekido et al, 1994;Remacle et al, 1999) and represses transcription by recruiting CtBP (Postigo and Dean, 1999). We therefore tested its potential as an Ecadherin repressor.…”
mentioning
confidence: 99%
See 1 more Smart Citation